Perbandingan Biaya dan Waktu Pelaksanaan Pekerjaan Pelat Lantai Metode Precast Half Slab, Full Slab dan Konvensional - Artiani, Gita Puspa; Indriasari; Dwi Lestari (Fakultas Teknik Universitas Krisnadwipayana, 2023)
Construction development in Indonesia continues to progress from year to year. One of the most expensive construction jobs is concrete floor slab work. This forces contractors to choose methods that save more costs and time. Therefore, this research aims to compare 3 methods, namely precast half slab, full slab and conventional methods which are quantitatively carried out by collecting data on project drawings, RAB and project schedule, then analyzed to get the total cost, time and volume of floor slab work. in each method using the Microsoft Excel 2021 program so that calculation results are obtained in terms of costs that are more effective and efficient by applying the precast half slab method for multi-storey building work scales. Where the precast half slab method requires a total cost of Rp. 4,159,526,137, the full slab method requires a total cost of Rp. 4,885,501,898 while the conventional method requires a total cost of Rp. 4,605,483,760. In terms of time, the full slab method is more effective with a total of 105 days of work, while half slab requires 150 days and conventional requires 210 days